Improved CARMA Locality Estimation Model for Peer List Reordering and Its Experimental Validation - Poryev, G.V.; Poryev V.A. (Реєстрація, зберігання і обробка даних, 2011)
The improvement of CARMA network model by addition of locality flavor as well as IPv6 support are concerned. The direct experimental evidence of the improvement of the efficiency of the peer-to-peer networks in terms of the network throughput using previously proposed CARMA locality awareness methods is established. The possible influences of the dynamics of the number of seeding and peering nodes in a swarm (including those directly connected to the test rig) are analyzed and taken into account. Main results indicate average 2,5 % improvement in transfer speed in comparison with clean unbiased transfer modes. Розглянуто вдосконалену реалізацію моделі CARMA, до якої додано новий клас локальності та обґрунтовано включення підтримки новітнього протоколу IPv6; також отримано пряме експериментальне підтвердження підвищення ефективності однорангових мереж із використанням попередньої версії оцінки локальності за моделлю CARMA. Проаналізовано та враховано вплив динаміки кількості завершених і незавершених вузлів у рої (включаючи ті, що прямо зв’язані з експериментальним стендом). Результати експериментів свідчать про підвищення середньої швидкості передачі на 2,5 % порівняно з немодифікованим режимом передачі. Рассмотрена усовершенствованная реализация модели CARMA, в которую добавлен новый класс локальности и обосновано включение поддержки новейшего протокола IPv6; также получено прямое экспериментальное подтверждение повышения эффективности одноранговых сетей с использованием предварительной версии оценки локальности по модели CARMA. Проанализировано и учтено влияние динамики количества завершенных и незавершенных узлов в рое (включая те, которые прямо связаны с экспериментальным стендом). Результаты экспериментов свидетельствуют о повышении средней скорости передачи на 2,5 % в сравнении с немодифицированным режимом передачи.